2018
DOI: 10.1093/jscr/rjy087
|View full text |Cite
|
Sign up to set email alerts
|

Haemangiopericytoma of the greater omentum: a rare tumour requiring long-term follow-up

Abstract: Haemangiopericytomas (HPC) are highly vascularized tumours located in any part of the body where capillaries can be found. Since 2002, they have been re-classified under the umbrella ‘extrapleural Solitary Fibrous Tumour (SFT)’ and the term HPC is nowadays used to describe a growth pattern rather than a clinical entity. Their biological behaviour varies and they require a long-term follow-up since they may recur or metastasise several years after successful treatment. We present the case of a gentleman with HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In 2009, Prakash et al [ 15 ] first reported peritoneal carcinomatosis caused by SFT tumor implants at the time of presentation, which is a rare metastasis route and is mostly observed in recurrent SFTs[ 13 , 25 ]. Several extra-pleural SFT cases with metastases after surgical excision in the greater omentum have been reported; 8 of the 14 cases reported in the literature involved metastasis or recurrence, and recurrence was observed even as long as 18 years after remission, or several times after resection[ 13 , 16 ]. Hence, long-term follow-up is necessary for patients who have SFT with malignant potential.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, Prakash et al [ 15 ] first reported peritoneal carcinomatosis caused by SFT tumor implants at the time of presentation, which is a rare metastasis route and is mostly observed in recurrent SFTs[ 13 , 25 ]. Several extra-pleural SFT cases with metastases after surgical excision in the greater omentum have been reported; 8 of the 14 cases reported in the literature involved metastasis or recurrence, and recurrence was observed even as long as 18 years after remission, or several times after resection[ 13 , 16 ]. Hence, long-term follow-up is necessary for patients who have SFT with malignant potential.…”
Section: Discussionmentioning
confidence: 99%
“…Some omental tumors, such as sarcoma, may recur and metastasize 20 years after surgery. Therefore, it is recommended that patients with omental tumors undergo long-term follow-ups after surgery[ 26 ]. In this study, although the postoperative pathology of this case was benign angiofibroma, we still recommended that the patient undergo active reexamination and follow-ups.…”
Section: Discussionmentioning
confidence: 99%